Study on the extension law of fractures in shale reservoirs under impact loads - Wei Li; Zhuolun Li; Ying Li; Huan Zhao; Shuangyang Wang; Xingsheng Xu; Jiahao Kong (PLoS ONE, 2025)
Fracturing technology is an important technique in the development of shale reservoirs. Compared with conventional hydraulic fracturing, explosive fracturing technology has the advantages of low cost and environmental protection. Relevant research results have shown that this technology can effectively improve the efficiency of shale oil and gas extraction. To further reveal the mechanism of reservoir fracture propagation under explosive fracturing, this paper conducted experimental research on the propagation law of complex fractures in shale reservoirs under impact load. The dynamic elastic modulus of shale samples was tested by using the Split Hopkinson Pressure Bar (SHPB) test system. A finite element model was established by using LS-DYNA software. Based on test results, the fracture propagation process was simulated under different impact loads, interlayer spacing, and fracture distribution conditions. The results indicate that the original crack zone of layered reservoirs is more prone to induce stress, which is beneficial for reservoir transformation in the near wellbore area, while explosive fracturing. The increase in interlayer spacing is beneficial for the expansion of the main crack, which can improve reservoir connectivity. As the impact load increases, the main cracks have better connectivity. This study can provide a theoretical basis for optimizing fracturing parameters and designing fracturing schemes, which is of great significance for the promotion of explosive fracturing technology and the efficient and environmentally friendly development of shale oil.